2023
DOI: 10.1039/d2ra07227k
|View full text |Cite
|
Sign up to set email alerts
|

2(1H)-Pyrazinones from acyclic building blocks: methods of synthesis and further derivatizations

Abstract: 2(1H)-Pyrazinones are found in natural and synthetic bioactive molecules. Methods for their synthesis by combining acyclic compounds are reviewed, from the earliest ones at the beginning of the 20th century to those described in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…It occurred to us that comparable zwitterions and thence comparable cycloadditions might be possible in an analogous pyrazine series, though an alternative route to 3-oxidopyraziniums 5 would be required ( Chemical Abstracts uses the term “3,4-dihydro-3-oxopyrazinium, inner salt”) (Scheme ). This concept was put into practice by accessing 3-oxidopyraziniums 5 from 2­(1 H )-pyrazinones 6 . Regioselective quaternization of the imine nitrogen of 2­(1 H )-pyrazinones 6 gives pyrazinium salts 7 , and then N-deprotonation reveals 3-oxidopyraziniums 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurred to us that comparable zwitterions and thence comparable cycloadditions might be possible in an analogous pyrazine series, though an alternative route to 3-oxidopyraziniums 5 would be required ( Chemical Abstracts uses the term “3,4-dihydro-3-oxopyrazinium, inner salt”) (Scheme ). This concept was put into practice by accessing 3-oxidopyraziniums 5 from 2­(1 H )-pyrazinones 6 . Regioselective quaternization of the imine nitrogen of 2­(1 H )-pyrazinones 6 gives pyrazinium salts 7 , and then N-deprotonation reveals 3-oxidopyraziniums 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This concept was put into practice by accessing 3-oxidopyraziniums 5 from 2(1 H )-pyrazinones 6 . 4 Regioselective quaternization of the imine nitrogen of 2(1 H )-pyrazinones 6 gives pyrazinium salts 7 , and then N-deprotonation reveals 3-oxidopyraziniums 5 . We showed that compounds 5 undergo ready dipolar cycloadditions with typical dipolarophiles like acrylates, acrylonitrile, vinyl sulfones, α,β-unsaturated ketones, and alkynyl esters.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazin-1­( 2H )-one core frameworks are important structural motifs in numerous bioactive heterocycles and natural products (Figure ). During the past few decades, the pyrazin-1­( 2H )-one pharmacophore has attracted great attention due to its broad biological activities in medicinal chemistry. Compounds containing the pyrazine-1­( 2H )-one core possess diversified biological activities such as antiviral, antitumor, antiparasitic, and antitubercular activities. , Hence, robust synthetic procedures through regioselective 6- exo -cyclization of propargyl amides to construct six-membered pyrazin-1­( 2H )-ones are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazinone scaffolds are a common motif in natural products with a broad range of biological properties, including kinase and protease inhibition and quorum sensing activity . They are found in all microbial domains of life, including the human microbiome, and play important roles as signaling molecules.…”
mentioning
confidence: 99%
“…1 Pyrazinone scaffolds are a common motif in natural products with a broad range of biological properties, including kinase and protease inhibition and quorum sensing activity. 2 They are found in all microbial domains of life, including the human microbiome, and play important roles as signaling molecules. Pyrazinones control biofilm formation in Vibrio cholerae, regulate the virulence of Staphylococcus aureus, and are involved in the pathogenesis of enterohemorrhagic Escherichia coli.…”
mentioning
confidence: 99%